VIPER: an industrially scalable high-current high-temperature superconductor cable. (7th October 2020) - Hartwig, Zachary S; Vieira, Rui F; Sorbom, Brandon N; Badcock, Rodney A; Bajko, Marta; Beck, William K; Castaldo, Bernardo; Craighill, Christopher L; Davies, Michael; Estrada, Jose; Fry, Vincent; Golfinopoulos, Theodore; et al.
Abstract: High-temperature superconductors (HTS) promise to revolutionize high-power applications like wind generators, DC power cables, particle accelerators, and fusion energy devices. A practical HTS cable must not degrade under severe mechanical, electrical, and thermal conditions; have simple, low-resistance, and manufacturable electrical joints; high thermal stability; and rapid detection of thermal runaway quench events. We have designed and experimentally qualified a vacuum pressure impregnated, insulated, partially transposed, extruded, and roll-formed (VIPER) cable that simultaneously satisfies all of these requirements for the first time. VIPER cable critical currents are stable over thousands of mechanical cycles at extreme electromechanical force levels, multiple cryogenic thermal cycles, and dozens of quench-like transient events. Electrical joints between VIPER cables are simple, robust, and demountable. Two independent, integrated fiber-optic quench detectors outperform standard quench detection approaches. VIPER cable represents a key milestone in next-step energy generation and transmission technologies and in the maturity of HTS as a technology.